(untitled) (Third Sector Social Economic Review, 2020)
In this study, the relationship between sustainable performance and financial performance of companies traded in DJSI emerging markets index is analyzed. In order to test this relationship, the reaction of investors to the stock returns according to the included, excluded and non-exluded of companies between 2013-2018, which is traded in the DJSI emerging markets index, is examined. In the study, the investor reaction to the stocks of the companies traded in the DJSI emerging markets sustainability index is analyzed by the ""event study"" method. In the study, included, excluded and non-excluded of companies to DJSI emerging markets index are analyzed in two stages according to announcement date and effective date. According to the results of the study, the reaction of the investors to the stocks of the companies included to the DJSI emerging markets index between 2013 and 2018 was negative, contrary to the expectations, and the companies excluded from the index were positive, except for 2014 and 2016. It was determined that investors did not react strongly to the stocks of companies that are non-excluded in the index, on around the announcement date and the effective date.